2009
DOI: 10.1007/s10900-009-9194-0
|View full text |Cite
|
Sign up to set email alerts
|

Health Indicators of Native Hawaiian and Pacific Islanders in the United States

Abstract: This study aimed to describe health indicators and behaviors of Native Hawaiian and Pacific Islander (NHPI) adults and to compare findings to previous reports on US NHPI and the US population. A sample of N = 100 (56 M, 44 F) NHPI adults aged 40–59 years completed an anonymous questionnaire addressing education and household income, tobacco use, physical activity, fruit and vegetable (F&V) consumption, cancer screening and health status. Objective measures of height and weight were taken to calculate body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 23 publications
(31 reference statements)
5
74
0
Order By: Relevance
“…Furthermore, NHPI have a higher prevalence of metabolic syndrome characteristics (diabetes, obesity, and/or lower HDL levels) compared with whites, which is consistent with prior studies. [10][11][12][13][14][15] In our study, NHPI with ischemic stroke were a decade younger than whites, a finding similar to the results of other observational ischemic stroke studies that compared non-Hispanic whites to Maoris from New Zealand, 21 Hispanics, 4,22 and blacks. 4,22 The higher burden of cardiovascular risk factors seen in NHPI is similar to the disparities seen among Hispanics and blacks, [5][6][7]22 and supports the idea that minority racial groups overall have a younger age of stroke onset and higher burden of cardiovascular risk factors compared with whites.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, NHPI have a higher prevalence of metabolic syndrome characteristics (diabetes, obesity, and/or lower HDL levels) compared with whites, which is consistent with prior studies. [10][11][12][13][14][15] In our study, NHPI with ischemic stroke were a decade younger than whites, a finding similar to the results of other observational ischemic stroke studies that compared non-Hispanic whites to Maoris from New Zealand, 21 Hispanics, 4,22 and blacks. 4,22 The higher burden of cardiovascular risk factors seen in NHPI is similar to the disparities seen among Hispanics and blacks, [5][6][7]22 and supports the idea that minority racial groups overall have a younger age of stroke onset and higher burden of cardiovascular risk factors compared with whites.…”
Section: Resultssupporting
confidence: 86%
“…For example, NHPI in the community have been shown to have higher prevalence of major cardiovascular risk factors [10][11][12][13][14][15] and die at a younger age from various cardiovascular disease-related complications compared with other major racial groups. 16,17 However, the specific disease burden related to ischemic stroke in the NHPI and Asian populations has not been studied.…”
mentioning
confidence: 99%
“…Research shows that level of education can affect physical activity levels, with more educated NHIPs being more likely to be physically active. 3,13 Low Health Literacy Health literacy is "an individual's ability to read, understand and use healthcare information to make decisions and follow instructions for treatment." 14 Research found that low health literacy was associated with poor diabetes outcomes in NHIP populations.…”
Section: Dietary Patternsmentioning
confidence: 99%
“…Finally, most NHPI culture places greater emphasis on the collective unit (e.g., community, group, family) rather than the individual. 13 Strategies should involve community and family members in the diabetes intervention process, so families and community members can understand the important role of regular physical activity and proper diet in diabetes prevention and provide support for NHPIs practicing a healthy lifestyle.…”
Section: Culturally Appropriate Strategies and Approachesmentioning
confidence: 99%
“…Similar to many institutions in Hawai'i, the study's host university is concerned with the well-being and status of Native Hawaiians, who tend to have poor health and life outcomes. Compared with the U.S. residents of European ancestry, Native Hawaiians and Pacific Islanders have higher rates of cancer, diabetes, infant mortality, HIV/AIDS, heart disease, obesity, adolescent suicide, and poverty; lower life expectancy; and lower levels of educational attainment (Moy, Sallis, & David, 2010; U.S. Department of Health & Human Services Office of Minority Health, 2011; Yuen, Nahulu, . Twenty three percent of the host university students are Native Hawaiian or part Native Hawaiian (Kakugawa-Leong, 2010), which is similar to the statewide figure.…”
mentioning
confidence: 99%